Burst-like reverse martensitic transformation during heating, cooling and under isothermal conditions in stabilized Ni-Ti-Nb. (15th April 2020) - Picornell, C.; Pons, J.; Paulsen, A.; Frenzel, J.; Kaminskii, V.; Sapozhnikov, K.; Van Humbeeck, J.; Kustov, S.
Abstract: To reveal mechanisms of martensite stabilization by prestrain in shape memory alloys, details of reverse martensitic transformation (MT) in prestrained Ni45 Ti46 Nb9 alloy were studied using calorimetry, dilatometry and resistivity. The first reverse MT is burst-like and is shifted to higher temperatures by ~120 K as compared to the nominal MT. During thermal cycling approaching the first reverse MT, stabilized martensite shows "forbidden" behaviours like burst-like reverse MT not during heating, but during cooling and under isothermal conditions. These unusual effects are attributed to non-thermoelastic nature of the first reverse MT in stabilized martensite under high chemical driving force. Graphical abstract: Image, graphical abstract